PROFIL KONDISI FISIK ATLET LARI JARAK JAUH KLUB ATLETIK BIMA CEPU KABUPATEN BLORA TAHUN 2020 (Universitas Negeri Semarang, 2021)
The problem of this research is how is the profile of the phisical condition of long distance running athletes in the Bima Cepu athletic club, Blora Regency in 2020? This research uses survey research and tets. Involving the population of athletic club athletes in Bima Cepu, Blora Regency. This study uses a sample of 20 long-distance running athletes. The method of analysis in this research is description quantitative. The results show that the on Velocity aspect, there is 1 athlete in â€œvery goodâ€ category, 2 athletes in â€œgoodâ€ category, 7 athletes in â€œmoderateâ€ category, 8 athletes in â€œpoorâ€ category and 2 athletes â€œvery poorâ€ category. On the Power aspect, there are 2 athletes in â€œvery goodâ€ category, 8 athletes in â€œgoodâ€ category, 4 athletes in â€œmoderateâ€ category, 2 athletes in â€œpoorâ€ category and 4 athletes in â€œvery poorâ€ category. On the Flexibility aspect, 8 athletes are categorized in â€œgoodâ€ category, 8 athletes in â€œmoderateâ€ category, and 4 athletes in â€œvery poorâ€ category. On the Endurance aspect, 12 athletes are included in â€œspecialâ€ category, 5 athletes in â€œvery goodâ€ category, 2 athletes in â€œgoodâ€ category, and 1 athlete in the â€œmoderateâ€ category. Atheletes are expected to be able to train optimally for the lack of physical condition components..